2017
DOI: 10.1002/hep.28947
|View full text |Cite
|
Sign up to set email alerts
|

The SRL peptide of rhesus rotavirus VP4 protein governs cholangiocyte infection and the murine model of biliary atresia

Abstract: Biliary atresia (BA) is a neonatal obstructive cholangiopathy which progresses to end stage liver disease, often requiring transplantation. The murine model of BA, employing rhesus rotavirus (RRV), parallels human disease and has been used to elucidate mechanistic aspects of a virus induced biliary cholangiopathy. We previously reported that RRV VP4 gene plays an integral role in activating the immune system and induction of BA. Utilizing rotavirus binding and blocking assays, this study elucidated how RRV VP4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…Further research led to the identification of a key amino acid sequence "SRL" in VP4, a sequence specific to those rotavirus strains that cause obstructive cholangiopathy (57). This tripeptide "SRL" on RRV VP4 was found to bind specifically to the cholangiocyte membrane protein heat shock cognate 70 (Hsc70), defining a novel binding site governing VP4 attachment (57). To gain insight into the mechanisms involved upon VP4-mediated infection, a reverse genetics system was developed to create a mutant of RRV with a single amino acid change in the VP4 protein and compared to that of wild-type RRV (where the arginine "R" in "SRL" region was replaced with glycine "G") (58).…”
Section: Evidence Of Viruses As a Causative Agent Of Bamentioning
confidence: 99%
“…Further research led to the identification of a key amino acid sequence "SRL" in VP4, a sequence specific to those rotavirus strains that cause obstructive cholangiopathy (57). This tripeptide "SRL" on RRV VP4 was found to bind specifically to the cholangiocyte membrane protein heat shock cognate 70 (Hsc70), defining a novel binding site governing VP4 attachment (57). To gain insight into the mechanisms involved upon VP4-mediated infection, a reverse genetics system was developed to create a mutant of RRV with a single amino acid change in the VP4 protein and compared to that of wild-type RRV (where the arginine "R" in "SRL" region was replaced with glycine "G") (58).…”
Section: Evidence Of Viruses As a Causative Agent Of Bamentioning
confidence: 99%
“…The basis for the reduction in replication is unclear; it may be a function of binding and entry but also may be a factor of how a virus traffics intracellularly following entry and how this, in turn, triggers the host immune response. Our previous data support this possibility, as we found that binding of arginine (R) to Hsc70 was required (33), which in turn governed translocation of RRV inside the cell. Alternatively, the mutant virus may not infect immune cells (dendritic cells), which also governs how the host immune system responds and has been shown to be a crucial step required for the development of BA (49).…”
Section: Discussionmentioning
confidence: 54%
“…We recently demonstrated that RRV utilizes the SRL region of its VP4 protein to bind to extracellular Hsc70 (33). Through blocking assays, we demonstrated that the peptide VSRLY is capable of blocking RRV's ability to bind to cholangiocytes.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations